Flexible regional economic integration in Africa: A historical look at the East African Community - Masiko, Timothy Bryan (2019)
Regional economic integration efforts in Africa have, over the years, yielded varied results. For the most part, they have not been as successful as hoped, often encountering crippling challenges. These challenges have been as varied as the blocs that have existed on the continent since the early colonial years. The main hindrance has been the considerably different abilities, intentions and political will with which regional economic integration has been approached. This, however, appears to have changed with the signing of the Treaty for the Establishment of the Africa Continental Free Trade Area (AfCFTA). The AfCFTA is Africa’s most ambitious effort geared at establishing the Africa Common Market (ACM) – an aspiration pursued incrementally since 1980.